PENGARUH PEMBERIAN KOMBINASI FRAKSI ETIL ASETAT AKAR PASAK BUMI DAN DOXORUBICIN TERHADAP BERAT BADAN DAN JUMLAN NODUL TIKUS SPRAGUE DAWLEY BETINA YANG DIINDUKSI 7,12 DIMETILBENZ(Î±) ANTRASEN (DMBA) - Laela Hayu Nurani; Achmad Mursyidi; Sitarina Widyarini (Pharmaciana, 2016)
Pasak Bumi roots contain quasinoid compounds that have carcinogenesis inhibitory, imunomudulator, antiulcer, and antimalaria effects. This study aims to determine the effect of a combination of ethyl acetate fraction of Pasak Bumi roots and doxorubicin on DMBA-induced white mice by weight and palpation observation. The mice were divided into 8 groups. Each group consisted of 7 female Sprague Dawley mice. Group 1 (normal) was only given food and drink, Group 2 was given fraction of ethyl acetate of Pasak Bumi roots (100 mg/kg body weight, Group 3 (positive control) was given doxorubicin (1.17 mg/kg body weight) 1 times a week for 5 weeks, Group 4 was given DMBA (20 mg/kg) two times a week for 5 weeks, Groups 5 was given DMBA (20 mg/kg) + doxorubicin (1.17 mg/kg), Group 6 was given DMBA (20 mg / kg) + ethyl acetate fractions of Pasak Bumi roots (100 mg / kg), Group 7 was given DMBA (20 mg / kg) + doxorubicin (1.17 mg / kg) + ethyl acetate fraction of Pasak Bumi roots (100 mg / kg) and Group 8 doxorubicin ( 1.17 mg / kg body weight) + ethyl acetate fraction of Pasak Bumi roots (100 mg / kg). Observations were made on the basis of body weight of mice and tumor incidence by palpation at week 6 of treatment. The result ofÂ  this research shows that the administration of ethyl acetate fraction of Pasak Bumi roots and doxorubicin combination can increase body weight of the mice and decrease the number of tumors compared to single doxorubicin.